The Relationship Between Parent Parenting Pattern and Toddler Development in Urung Purba Village, Purba District, Simalungun Regency - Dilla Sastia Mara; Pasaribu, Doni Saputra (PT Inovasi Pratama Internasional, 2023)
Child development is strongly influenced by the environment and interactions between children and their parents Data obtained in the Urung Purba Village in 2019 the number of children under five was 172 children spread across the Urung Purba Village. To find out the relationship between parenting styles and the development of toddlers in Unung Purbakabupaten Simalungun Village in 2019. The type of research used in this research is a quantitative study using a cross-sectional design with a population of all children under five in the working area of the Ranometo Health Center. The technique used in sampling is Smafied sampling so that a sample of 72 respondents is obtained Data analysis with the chi square test at a 95% level of confidence (a-0.05) It is hoped that there will be counseling to parents about the importance of providing proper parenting so that it supports the development of their children.